Investigation of Clay Type on Low Salinity Water Flooding Using a Glass Micromodel - Wei, Xuemei; Jiang, Wenchao; Zhang, Yanyu; Wang, Zhao; Li, Xiaojun; Wu, Feipeng (Frontiers in Energy Research, 2020)
Clay minerals are usually regarded as an important factor affecting the results of low salinity water (LSW) flooding. However, experiments on clay minerals are mainly in qualitative stage, the mechanism of clay minerals has not been studied completely. In this paper, Zeta potential of four kinds of clay minerals (montmorillonite; chlorite; illite; kaolinite) in different brine was measured, microscopic models of these clay minerals were made to measured wetting angle in different brine, and montmorillonite and kaolinite were chosen to conduct microscopic displacement experiments through customized micro-glass etching models. From experiment results, the following conclusions can be get: 1). With the decrease of salinity of injected water, the negative zeta potential of clay minerals increases and the wetting angle decreases. 2). Clay minerals are more sensitive to monovalent Na+ than bivalent Ca2+. 3). The results of microscopic experiments show that LSW can effectively improve oil recovery, whether kaolinite or montmorillonite. The recovery of montmorillonite is better with a relatively high salinity of LSW and kaolinite is better with a relatively low salinity of LSW. The mechanism of LSW improves kaolinite recovery factor is the change of wettability while that of montmorillonite is the increase of water phase wettability. However, a lot of droplet-like residual oil cannot be displaced in the montmorillonite throat. In filed production, both kaolinite-rich and montmorillonite-rich reservoirs are suitable for LSW flooding to improve oil recovery. However, for kaolinite reservoirs, a lower salinity of injected water would produce a better result, while for montmorillonite reservoirs, residual oil droplets in the throat are noteworthy.